2014
DOI: 10.17017/jfish.v2i2.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status of fishermen of the Marjat Baor at Kaligonj in Jhenidah district, Bangladesh

Abstract: This study was carried out to assess the socio-economic status of fishermen of the Marjat Baor at Kaligonj of Jhenidah district. Fifty fishermen from 50 families were interviewed. Results revealed that 94% respondents were married and age varied between 30 and 45 years. Almost all the fishermen were Hindus (96%). Most of the people of the community were illiterate (60%) and among all of the school going children (58%) were boys and (42%) were girls. Above fifty percent people lived in nuclear family. 40% peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
7
8
0
1
Order By: Relevance
“…Hossen et al (2020a) reported that 60% of fishers were illiterate, 30% were sign only, 8.33% were primary level and 1.67% had only secondary level education in Kirtankhola River, Southern Bangladesh. Similar results also reported by Bappa et al (2014) that the majority of fishers (60%) were illiterate in the Marjat Baor at Kaligonj in Jhenidah district. It was found that 32.5% of peoples were Illiterate, 40 % can sign only, 15% were primary level, 7.5% were secondary level, and 5% were higher secondary and above in the Eshulia Beel at Gouripur Upazila, Mymensingh (Rahman et al, 2016b).…”
Section: Educational Statussupporting
confidence: 89%
“…Hossen et al (2020a) reported that 60% of fishers were illiterate, 30% were sign only, 8.33% were primary level and 1.67% had only secondary level education in Kirtankhola River, Southern Bangladesh. Similar results also reported by Bappa et al (2014) that the majority of fishers (60%) were illiterate in the Marjat Baor at Kaligonj in Jhenidah district. It was found that 32.5% of peoples were Illiterate, 40 % can sign only, 15% were primary level, 7.5% were secondary level, and 5% were higher secondary and above in the Eshulia Beel at Gouripur Upazila, Mymensingh (Rahman et al, 2016b).…”
Section: Educational Statussupporting
confidence: 89%
“…The annual average income of the fishers in the current study area is presented in Table 5. The result supports Trina et al (2016) that 70% peoples earned 40,000-60,000 BDT/year, 20% earned 61,000-99,000 BDT/year and 10% earned 100,000-above BDT/year and also agrees with Bappa et al (2014) that annual household income of maximum beneficiaries (44%) was below 30,000 BDT and above 50,000 BDT found in only 4% cases.…”
Section: Annual Average Income Of Fishers In the Study Areasupporting
confidence: 89%
“…Activity during ban period is presented in Table 2. The result supports Bappa et al (2014) that primary occupation of 60% respondents was fishing and few were also involved in agriculture. They noted that only 12% women were engaged in making nets for fishing.…”
Section: Demographic Information Of the Fisherssupporting
confidence: 79%
“…Verite [8] reported that approximately 46.6 percent of respondents were male and 53.3 percent of respondents were female. From this study, 57% labor had passed primary level, about 13% had secondary level, there had no any S.S.C, HSC educational level labor in hatchery, and about 30% were illiterate but Bappa, et al, [9] reported that the illiteracy level of majority fishermen (60%) in the study area was found illiterate and only a small portion (10%) passed SSC/HSC examinations. In the study area, it was found that 22% labor live in Nuclear family, 88% live in joint family.…”
Section: Discussionmentioning
confidence: 59%